Comparison of Icelandic and Danish managers’ evaluation of their working environment in light of Nordic values - Arnórsdóttir, Bergþóra Hlín; Svansson, Einar; Joensen, Kári (Stjórnsýslustofnun, 2017)
Nordic leadership values have gained increased publicity and popularity recently. The paper looks at Icelandic public management. The main research question is if and how Icelandic managers adhere to Nordic leadership values. The research is based on a prior Danish study: Public managers – tasks and opinions. An online questionnaire was sent to 1.685 public managers in Iceland, with 524 respondents so the participation rate is 31%. The main purpose of the research was to highlight the emphasis of Icelandic managers in daily tasks and get their opinions on their working environment and regulatory framework. Another point was to compare the public working environment in Iceland and Denmark regarding the basic values of Nordic leadership. The main findings show that public management in Iceland is characterized by trust, clear work-processes, short chains of command and minimal bureaucracy. Cooperation and social networking at the workplace was positive and reasonable demands towards the managers. At the same time, there seem to be opportunities for the managers to have more influence to enhance performance in their institutions. The main barriers were minimal influence on legislation and the political stakeholders. In comparison, the Danish managers thought bureaucracy too burdensome and that work-processes could be simplified. However, the Danish managers feel they have greater impact and influence on their working environment and political stakeholders. The work-processes and perspectives of Icelandic managers are in line with the Nordic management values: Open communication, critical thinking and care. Norræn forysta byggir á gildum sem notið hafa aukinnar athygli og vinsælda. Viðfangsefni greinarinnar er að fjalla um opinbera stjórnun á Íslandi og skoða hvort og þá með hvaða hætti íslenskir stjórnendur falla að gildum norrænnar forystu. Gerð var rannsókn að danskri fyrirmynd sem nefnist Opinberir stjórnendur – verkefni og viðhorf. Spurningalisti í formi vefkönnunar var lagður fyrir 1.685 opinbera ...